Application of the Islamic Jurisprudence Principles Prohibiting Gharar in the Sharia Government-Business Entity Cooperation (KPBU) Scheme - Wafa Umniati; Ali Sajad; Tasha Vinaza (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2026)
Background: This study aims to examine how the legal maxim al-gharar al-kathīr yufsidu al-‘uqūd dūna yasīrihī is manifested in DSN-MUI Fatwa No. 156/DSN-MUI/V/2023 concerning the implementation of Sharia principles in infrastructure provision activities through the Government–Business Entity Cooperation (KPBU) scheme based on availability payment. Method: This study employs a library research method focusing on the examination of documents containing data on the implementation of the prohibition of gharar in fiqh muʿāmalah māliyyah, particularly in DSN–MUI fatwas. Results: The findings indicate that Fatwa DSN No. 156/DSN-MUI/V/2023, especially in the section concerning the contents of KPBU contractual documents, contains elements of uncertainty (gharar). Conclusion: Such gharar falls under the category of gharar yasīr, which does not invalidate or compromise the contract, in accordance with the fiqh maxim al-gharar al-kathīr yufsidu al-ʿuqūd dūna yasirihi